2001
DOI: 10.1128/aac.45.1.150-157.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oral Acyclovir in Neonates and in Infants: a Population Analysis

Abstract: Acyclovir is approved for the treatment of herpes simplex virus (HSV) and varicella-zoster virus (VZV)infections in children by the intravenous and oral routes. However, its use by the oral route in children younger than 2 years of age is limited due to a lack of pharmacokinetic data. The objectives of the present study were to determine the typical pharmacokinetics of an oral suspension of acyclovir given to children younger than 2 years of age and the interindividual variabilities in the values of the pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 19 publications
(23 reference statements)
6
54
0
1
Order By: Relevance
“…(33). In addition, a few reports regarding the use of VCV and ACV in humans have shown that the duration that the ACV concentration in plasma remains above a given threshold is an important criterion for antiviral efficacy (34)(35)(36). Although differences existed in the PD parameters and analysis conditions between these previous reports and our present nonclinical PK/PD analysis, the results obtained using a murine infection model are consistent with those of clinical PK/PD analysis.…”
Section: Figsupporting
confidence: 71%
“…(33). In addition, a few reports regarding the use of VCV and ACV in humans have shown that the duration that the ACV concentration in plasma remains above a given threshold is an important criterion for antiviral efficacy (34)(35)(36). Although differences existed in the PD parameters and analysis conditions between these previous reports and our present nonclinical PK/PD analysis, the results obtained using a murine infection model are consistent with those of clinical PK/PD analysis.…”
Section: Figsupporting
confidence: 71%
“…The PK/PD index that was used was the time that the concentration remained above the EC 50 , defined as the cumulative percentage of time over a 24-h period that the drug concentration exceeds the EC 50 (4). This is expressed as a percentage of the dosage schedule, which is the PK/PD breakpoint and which should be more than 50% (26).…”
Section: Vol 51 2007 Pharmacokinetics Of Acyclovir In Horses 4309mentioning
confidence: 99%
“…The second aim was to combine PK and pharmacodynamic (PD) information to design an optimal dosage regimen so that plasma concentrations exceed the EC 50 value of EHV-1 during the entire treatment interval. This is based on the reasoning that an antiviral drug should be effective when the plasma level exceeds the EC 50 value of the virus determined in vitro (8,26).…”
mentioning
confidence: 99%
“…L'utilisation de connaissances a priori sur les processus de maturation de la clairance rénale chez le nourrisson a pu être illustrée lors de l'optimisation du plan expérimental d'un médicament antiviral. [21] Elle a conduit à l'ajustement des temps de prélèvement sur l'âge gestationnel. Le partage d'information et le concept de mise en connexion des mondes adultes et pédia-triques ont pu être illustrés aussi à l'occasion de la construction d'un modèle pharmacocinétique de population pour la ciclosporine en pédiatrie.…”
Section: La Modélisation Intégrant Les Connaissances a Prioriunclassified